Quantification of niclosamide polymorphic forms - a comparative study by Raman, NIR and MIR using chemometric techniques - Bhavana, Valmala; Chavan, Rahul B.; Mannava, M. K. Chaitanya; Nangia, Ashwini; Shastri, Nalini R. (Talanta, 2019)
Niclosamide, an anthelmintic drug recently repurposed for its activity against cancer, crystallizes into three solvated forms, two monohydrates (NHa, NHb) and one anhydrous (NAn) form. NAn is sensitive to pseudopolymorphic transformations that affect its dissolution and consequently, its bioavailability. NAn exhibits a polymorphic conversion to metastable monohydrate (NHa) form during high-energy milling in presence of poorly soluble solvents like water. It is hence very important to quantify polymorphic conversion from NAn to NHa, as water is a commonly used solvent during various processing like ball milling and wet granulation. This main objective of the study was to examine the feasibility of Raman, NIR and MIR spectroscopic techniques for identification and quantification of polymorphic forms of niclosamide in binary mixtures and multicomponent mixtures. Calibration models were developed and validated by vibrational spectroscopic techniques in binary mixtures of NAn and NHa and in multicomponent mixtures by chemometric techniques. These techniques were further used to identify and quantify NHa during ball milling, granulation and in presence of other polymorphic forms of niclosamide. Identification and quantification of pseudopolymorphs in binary and multicomponent mixtures with an acceptable recovery of 100.13-102.99% for Raman and 100.07-101.28% for NIR with low % RSD of 2.38-3.12 for both techniques were obtained. The % NHa determined during ball milling and granulation was similar by NIR and Raman. Raman spectroscopy however showed a greater advantage over other techniques in determining the NHa in presence of NHb due to significant difference in the spectral region of hydrates, when compared to NIR and MIR.
Keywords: Ball milling; Granulation; MSC; PLS; Polymorphic conversion; spectroscopy

Solvent-free hydroxylation of unactivated C-H bonds in small molecules and macromolecules by a Fe complex - Chatterjee, Debasmita; Sajeevan, Amritha; Jana, Sandipan; Birajdar, Rajkumar S.; Chikkali, Samir H.; Sivaram, Swaminathan; Sen Gupta, Sayam (ACS CATALYSIS, 2024)
Keywords: Ball milling; solid-state C-H hydroxylation